The sound of education: Exploring Filipino students' perceptions of teachers' vocal quality in the classroom - Calinao, Jake; Alvarez, Kris Ann; Velarde, Christel; Padullon, John Michael; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
Every teacher needs to develop their vocal skills through continual practice and voice quality improvement. Students will draw judgments and assumptions about the teacher's attitude toward them, as well as the knowledge and concepts that he or she is imparting, based on the tones of the teacher's voice. The purpose of this study was to explore students’ perception on teachers’ vocal quality in a classroom setting. With a qualitative research design, the current study employed an interpretative phenomenological analysis approach. The participants of the study are composed of 26 students (9 males) (17 females) under the College of Business and Entrepreneurship. The collection of data was done through a face-to-face, semi-structured interview with audio recording. With the help of thematic analysis, the researchers come up with these themes: (1) the instructional tone or manner and emotional expression of the teachers; (2) teachers’ emphasis and motivation on teaching; (3) engagement and voice characteristics of teachers; (4) teachers’ effectiveness and students’ engagement in the classroom; (5) challenges faced by students; (6) comprehensibility and academic performance of students; and (7) learning and knowledge acquisition of students. The findings revealed that the vocal quality of teachers have an impact on how engaged their students are in the learning process, which in turn helps them achieve academically.